Academic Supervision of the School Principal In Improving the Professionalism of SD Negeri Tlogo Teachers - Sarida Nur Asani; Belita Yoan Intania; Ani Rusilowati (Journal on Education, 2023)
The professionalism of educators refers to the continuous development of strategies, which are used in carrying out work in accordance with their profession, with the aim of increasing their professional abilities. Professional teachers have four competencies which include pedagogic competence, social competence, personal competence and professional competence. However, sometimes there are teachers who have difficulty adjusting the knowledge, skills and abilities they have with the learning needs in the classroom. In addition, the curriculum changes that have occurred require teachers to continue to develop and innovate learning activities that are adapted to the applicable curriculum. So, in this case the teacher needs coaching, debriefing, guidance and supervision in improving their professional abilities. Research conducted at SD Negeri Tlogo used a qualitative approach, with data collection techniques by means of observation, interviews and documentation, showing the implementation of academic supervision by the principal of SD Negeri Tlogo in increasing professionalism with a good reputation with a percentage of mastery of pedagogic competencies of 85%, mastery of personality competencies of 85%, mastery of social competence by 85% and mastery of professional competence by 86%.